Elderly Nutrition Status In Caringin Health Center Posbindu - Citra Windani Mambang Sari; Clara Dwi Amri; Titin Dwi Sutini (Universitas Padjadjaran, 2019)
Elderly is one of the most vulnerable groups to nutritional problems. Elderly people should maintain nutritional status at optimum conditions, so they can help their physical condition in the process in adjusting to the changes they experience. The purpose of this study was to determine the description of the nutritional status of the elderly at Posbindu Caringin Health Center. The research method was descriptive using a cross-sectional approach. The number of respondents was 125 people that chosen using purposive sampling technique. Data collection using a Mini Nutrition Assessment questionnaire and analyzed using percentage and frequency distribution. The study found that the elderly had normal nutritional status (68.0%), the risk of malnutrition (27.2%), and malnutrition (4.8%). The conclusions in this study are the nutritional status of the elderly in Posbindu Pusingin Caringin, most of the elderly have normal nutrition. Community nurses are expected to be able to use this information in determining appropriate interventions and prevention related to the nutrition problems of the elderly.